Calculating the cost of congestion to society: A case study application to Flanders. (September 2022) - Struyf, Els; Sys, Christa; Van de Voorde, Eddy; Vanelslander, Thierry
Abstract: Road congestion is an issue that has received growing attention in all big economic activity centers around the world. Congestion seems to be inextricably linked to economic growth, and is therefore considered a sign of strong economic performance. However, at the same time, it reflects a problem of lack of matching between demand for and supply of transport capacity, risking to suffocate the economic system. A problem is that the external congestion costs are not included in the price of transport, mainly because it is hard to accurately calculate them, due to the absence of an approach to do so. This paper creates a globally accepted approach for calculating the impact of congestion on costs, both operational and societal. It does so by first of all learning from defining the relevant concepts, based on literature and an expert meeting that was hosted. It shows the components of congestion costs, which comprise both private and societal elements, direct and indirect, and it also identifies that transport can be split up in truck, van, work-related and private trips, each of which has its relevant cost characteristics. Furthermore, an own instrument for congestion cost calculation is elaborated and applied to and validated on a specific Flemish congestion situation. The instrument provides uniform insight into the magnitude and impact of congestion in a specific area or on a specific road. The resulting monetary values can first of all be used in negotiations by trucking companies with customers, for agreeing on transparent calculation of congestion surcharges. The results can also be used for determining a company location where congestion impacts are lower. Finally, resulting monetary values can be used by producers to see how competitive are the alternative modes rail and barge in terms of total generalized costs, not based on theoretical figures, but on calculations taking into account real cost and time impacts. Policymakers can use the results first of all to identify areas where the impact of congestion is high, and which should get priority in setting up solutions. Second, they can use the instrument and its results to test the effect of congestion mitigation measures (e.g. road pricing).